Assisting the management of digital library in Tegal Harum Village Denpasar - Denok Lestari; Ni Luh Supartini; Ni Made Ayu Sulasmini; I Putu Edy Suardiyana Putra (Universitas Muhammadiyah Magelang, 2022)
This community service activity under the scheme of applying science and technology for the community is in partnership with the village of Tegal Harum, Denpasar Bali, in the field of digital library management. The Sastra Mahottama Library in Tegal Harum Village, apart from providing conventional services, also provides digital library services through the SIPESAT application (Digital Library Application) in Tegal Harum Village, which makes it easier for people to borrow various types of e-books according to their needs. Problems faced by the library managers are related to the classification and cataloguing of library materials, as well as increasing the capacity of human resources for digital library managers. The implementation using the classical and individual methods lasts for one month at the Tegal Harum village office. Activities consist of situation analysis, training, and evaluation stages. The implications of service activities are the results of the classification and cataloguing of 30% of reading collections as well as increasing knowledge and skills in using digital library applications.